Association between communication deviance of adoptive parents and formal thought disorder of adoptee when the length of parents' speech is standardized in different ways - Kivikangas, Helmi; Seppälä, Satu (2012)
Communication Deviance (CD) is considered to be a potential environmental factor in gene-environment interaction leading to offspring psychopathology, for example thought disorders and mental disturbances. The aim of this study was to examine the relationship between formal thought disorder of genetic high-risk and low-risk adoptees and Communication Deviance of adoptive parents when the length of their speech is standardized with spoken words (Word Count, WC). The sample included a group of 58 adoptees at high genetic risk for schizophrenia spectrum disorders and a comparison group of 96 low-risk adoptees and their adoptive families. Communication Deviance (CD) of the adoptive parents was assessed by measuring their frequencies of CD. The scores were standardized by dividing them by the number of spoken words (Word Count, WC). Thought disorders of the adoptees were measured by the Index of Primitive Thought scale (IPT). CD scores and WC measures correlated highly and significantly with each other. When CD was standardized by diving the score by the number of words, there was no interaction between genetic risk of adoptees and CD of adoptive parents that would explain thought disorder in adoptees. Length of speech may be an essential part of Communication Deviance, indicating that high verbosity could in itself be unclear communication. Standardization of CD makes the scores of the subjects comparable, but dividing CD scores by word count seems to conceal the gene-environment interaction. Further, CD score standardized by dividing by number of transactions (responses) instead of words may represent CD more accurately, when each Rorschach response is thought as an attempt to share one meaning unit with another person. In this case CD score of a response reflects the failure in this sharing.